Soundings in Atlantic history : latent structures and intellectual currents, 1500-1830 - Bailyn, Bernard; Denault, Patricia L. (Harvard University Press, 2009)
Drawn together in a comprehensive Introduction by Bernard Bailyn, these innovative essays include analyses of the climate and ecology that underlay the slave trade, pan-Atlantic networks of religion and commerce, as well as the inter-ethnic collaboration in the development of tropical medicine, science as a product of imperial relations, and the awareness of the Atlantic world in the mind of David Hume.